Amyotrophic lateral sclerosis patients show increased peripheral and intrathecal T-cell activation. Issue 3 (14th July 2021) - Rolfes, Leoni; Schulte-Mecklenbeck, Andreas; Schreiber, Stefanie; Vielhaber, Stefan; Herty, Michael; Marten, Anika; Pfeuffer, Steffen; Ruck, Tobias; Wiendl, Heinz; Gross, Catharina C; Meuth, Sven G; Boentert, Matthias; et al.
Abstract: Several studies suggest a role for the peripheral immune system in the pathophysiology of amyotrophic lateral sclerosis. However, comprehensive studies investigating the intrathecal immune system in amyotrophic lateral sclerosis are rare. To elucidate whether compartment-specific inflammation contributes to amyotrophic lateral sclerosis pathophysiology, we here investigated intrathecal and peripheral immune profiles in amyotrophic lateral sclerosis patients and compared them with controls free of neurological disorders (controls) and patients with dementia or primary progressive multiple sclerosis. Routine CSF parameters were examined in 308 patients, including 132 amyotrophic lateral sclerosis patients. In a subgroup of 41 amyotrophic lateral sclerosis patients, extensive flow-cytometric immune cell profiling in peripheral blood and CSF was performed and compared with data from 26 controls, 25 dementia and 21 multiple sclerosis patients. Amyotrophic lateral sclerosis patients presented with significantly altered proportions of monocyte subsets in peripheral blood and increased frequencies of CD4 + and CD8 + T cells expressing the activation marker HLA-DR in peripheral blood (CD8 + ) and CSF (CD4 + and CD8 + ) compared with controls. While dementia and multiple sclerosis patients exhibited a comparable increase in intrathecal CD8 + T-cell activation, CD8 + T-cell activation in the peripheral blood in amyotrophic lateral sclerosis was higher than in multiple sclerosis patients. Furthermore, intrathecal CD4 + T-cell activation in amyotrophic lateral sclerosis surpassed levels in dementia patients. Intrathecal T-cell activation resulted from in situ activation rather than transmigration of activated T cells from the blood. While T-cell activation did not correlate with amyotrophic lateral sclerosis progression, patients with rapid disease progression showed reduced intrathecal levels of immune-regulatory CD56 bright natural killer cells. The integration of these parameters into a composite score facilitated the differentiation of amyotrophic lateral sclerosis patients from patients of all other cohorts. To conclude, alterations in peripheral monocyte subsets, as well as increased peripheral and intrathecal activation of CD4 + and CD8 + T cells concomitant with diminished immune regulation by CD56 bright natural killer cells, suggest an involvement of these immune cells in amyotrophic lateral sclerosis pathophysiology. Abstract : Rolfes et al. reported increased frequencies of activated T cells in the peripheral blood and cerebrospinal fluid of amyotrophic lateral sclerosis patients. They provided evidence that patients with rapid disease progression have reduced intrathecal levels of immune-regulatory CD56 bright NK cells, suggest an involvement of these cells in disease pathophysiology. Graphical Abstract: